Study on Designing and Operational Analysis of Wet Clutch (International Journal of Scientific Research and Management (IJSRM), 2017)
A wet clutch, which is an oil-lubricated friction type device, a torque transmission or torque holding device. It is commonly employed in a planetary gear-based automatic transmission system. Wet clutch is also found as a vehicle launch device. Although the wet clutch technology has been around years. In this paper an automobile clutch plate system is designed and analysis requirement of clutch high torque and high control accuracy and batter design. The paper deal with design friction clutch and analysis. The measurement result show that the torque efficiency and accuracy improve and system is working credibly and stable to improve the engagement quality of clutch plate. The purpose of a clutch is to initiate motion or increase the velocity of body generally by transferring kinetic energy from another motion body. The mass being accelerated is generally a rotating inertial body’